ESTRUCTURA Y EVOLUCIÓN DE DOS MASAS MIXTAS DE FRONDOSAS PROCEDENTES DE UN ANTIGUO MONTE ADEHESADO - Hermosilla, D; Pardo, F; Gil, L; Pardos, J A (III Congreso Forestal Español Congreso, 2001)
The presence of an important number of deciduous Central European species in Hayedo de Montejo makes it to be considered a singular place in Madrid. Past traditional practices conditioned the present characteristics of this forest. Two mixed deciduous stands were chosen for its study, both formed by a stratum of old-growth trees and another made up of poles. A vegetation inventory was made around twenty old-growth trees. The influence in the structure and evolution of the stand composed by poles was studied. The species of old-growth tree and the distance were relevant on the structure of the stand grown around them.
Keywords: competition; open wood; shade tolerance